2010
DOI: 10.1111/j.1365-2435.2010.01794.x
|View full text |Cite
|
Sign up to set email alerts
|

Plant traits that predict resistance to herbivores

Abstract: Summary1. Although secondary metabolites are recognized as fundamental to the defence of plants against insect and mammalian herbivores, their relative importance compared to other potential defensive plant traits (e.g. physical resistance, gross morphology, life-history, primary chemistry and physiology) are not well understood. 2. We conducted a meta-analysis to answer the question: What types of genetically variable plant traits most strongly predict resistance against herbivores? We performed a comprehensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
450
3
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 466 publications
(489 citation statements)
references
References 89 publications
30
450
3
6
Order By: Relevance
“…Our fi ndings show the relevance of considering more than one foliar attribute to predict the interaction patterns in a plant-herbivore network, as has been documented when predicting herbivore damage ( Agrawal and Fishbein, 2006 ;Carmona et al, 2011 ;Loranger et al, 2012 ;Schuldt et al, 2012 ). Our results suggest that leaf mechanical traits (toughness and trichome density) were better predictors of plant species strength and herbivore selectiveness than the percentage of oxidized phenolics.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Our fi ndings show the relevance of considering more than one foliar attribute to predict the interaction patterns in a plant-herbivore network, as has been documented when predicting herbivore damage ( Agrawal and Fishbein, 2006 ;Carmona et al, 2011 ;Loranger et al, 2012 ;Schuldt et al, 2012 ). Our results suggest that leaf mechanical traits (toughness and trichome density) were better predictors of plant species strength and herbivore selectiveness than the percentage of oxidized phenolics.…”
Section: Discussionsupporting
confidence: 52%
“…Chemical and physical resistance traits of plants aff ect the foraging behavior and performance of herbivores, infl uencing the magnitude of their interaction with diff erent host plants ( Coley and Barone, 1996 ;Pilson, 2000 ;Poelman et al, 2008 ;Fatouros et al, 2014 ). For example, leaf toughness is a physical barrier ( Lucas et al, 2000 ;Read and Stokes, 2006 ;Peeters, 2007 ) that is highly correlated with herbivore damage ( Coley, 1983 ) and offers effective resistance against herbivores ( Summerville and Crist, 2003 ;Hanley et al, 2007 ;Clissold et al, 2009 ;Carmona et al, 2011 ). Trichomes constrain the movement of herbivores and aff ect larval consumption and survival ( Zalucki et al, 2002 ;Handley et al, 2005 ;Tian et al, 2012 ) and oft en exudate toxic chemicals ( Lin et al, 1987 ).…”
Section: Study Site -Fieldwork Was Done At the Centro De Investigacionesmentioning
confidence: 99%
“…Phenology also is tied to herbivore performance: the main herbivores are able to eat off a tree only during certain stages of the phenology. If the phenology is genetically determined, trees sampled at the same time may have different chemical profiles simply because they differ in phenology (Carmona et al, 2011). Studying individual traits separately may not lead to ecologically relevant results.…”
Section: Discussionmentioning
confidence: 99%
“…These changes in chemistry indirectly affect herbivory (Bryant et al, 1983). In addition to chemical variability as such, the rate at which the phenology proceeds during the spring and summer may also have a genetic basis, and this too may play an important part in herbivory defense (Carmona et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A study of cocoa plants in Ghana showed that syrphid abundance correlates positively with aphid abundance [10]. Conspecific plants experience differences in herbivore susceptibility due to variations in phenological, morphological and chemical defense traits [11]. It is therefore possible that the altered morphology and heightened defense response of introduced hybrid coffee varieties could affect herbivore feeding behavior.…”
Section: Study Speciesmentioning
confidence: 99%